Penas alternativas e a ressocialização: há eficácia? - Guedes, Júlia Valdivia (2024)
This thesis aims to analyze alternative penalties within the context of the Brazilian penal system, focusing on their importance for human dignity and as a possible solution to the prison system crisis. The starting point is the observation that imprisonment, in its traditional form, has failed to fulfill its preventive and resocializing functions. Alternative penalties are emerging as a global phenomenon, a trend that seeks to contain crime through mechanisms that go beyond mere retribution for damages, aiming to rehabilitate the offender and promote social reintegration. The effective application of these measures contributes to the resocialization of those convicted of minor offenses, in addition to helping reduce prison overcrowding, a serious problem plaguing the Brazilian prison system. The general objective of this work is to discuss the current conditions of the penal system and analyze alternative penalties as possible solutions to the crisis faced. For this, an analysis of comparative and Brazilian legislation will be carried out, addressing the difficulties in applying custodial sentences, as well as the effectiveness of alternative penalties. The different types of alternative penalties present in the Brazilian legal system will also be characterized. The methodology used will be the deductive method, based on theoretical research, seeking to build a critical and reflective analysis on the topic, contributing to the debate on the reform of the penal system and the search for a more just, humane, and effective model